APLIKASI PENGINDERAAN JAUH MULTITEMPORAL UNTUK MONITORING KEJADIAN UPWELLING DI PERAIRAN BAGIAN SELATAN PULAU JAWA - LAUT TIMOR - , ISMAIL PRATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research are to determine sea surface temperature (SST) and chlorophyll-a concentration variability, mapped the upwelling events during 2004 to 2013 and also determine upwelling duration of the WPP RI 573. Classification method is used to mapped upwelling area when SST around 25-28 0C and chlorophyll-a around 0,7-10 mg/m3. It also used transect line to determine SST and chlorophyll-a variability. The result showed that generally upwelling events at WPP RI 573 start from coastal region at south of East Java and Bali. Upwelling zone expansion affected by surface wind, the faster the wind blows resulted in the rise of Ekman transport. Upwelling movement at WPP RI 573 affected by ocean surfce current . While El nino and IOD +, SST is colder than normal years so it caused intensity and area of upwelling become rised with duration during Juni to Oktober. Whereas La nina and IOD +, SST is hotter than normal years so it caused intensity and area of upwelling become descend with duration during July to Oktober